Cost of technological products: essential security - Chernyshenko, O. I. (Wydawnictwo Wyższej Szkoły Technicznej w Katowicach, Poland, 2024)
A study of the theoretical and methodological essence of the term "cost of a technological product" was conducted. It is proved that the theoretical and methodical definition of cost largely depends on the scope of its consideration and use, to which the author includes economic theory, accounting, financial management and international standards of financial reporting. It has been proven that the cost price of a technological product is most often used as an economic category and as an important indicator of the economic activity of an enterprise. Two sufficiently independent methodological approaches to the interpretation of the term cost of industrial production have been identified and substantiated - political-economic and marginalist. An analytical study of these approaches has been carried out.
Собівартість технологічної продукції: сутнісне забезпечення
Keywords: costs; technology; definition; economic category; технологічні продукти; собівартість; ринкова економіка; промислові підприємства; витрат підприємства